A semi-automated virtual workflow solution for the design and production of intraoral molding plates using additive manufacturing: the first clinical results of a pilot-study - Grill, Florian D.; Ritschl, Lucas M.; Bauer, Franz X.; Rau, Andrea; Gau, Dominik; Roth, Maximilian; Eblenkamp, Markus; Wolff, Klaus-Dietrich; Loeffelbein, Denys J. (Scientific Reports, 2018)
Computer-aided design and computer-aided manufacturing (CAD/CAM) technology has been implemented in the treatment of cleft lip and palates (CLP) by several research groups. This pilot study presents a technique that combines intraoral molding with a semi-automated plate generation and 3D-printing. The clinical results of two intraoral molding approaches are compared. This is the first clinical investigation of semi-automated intraoral molding. Our study included newborns with unilateral CLP. Plaster models were digitalized and measured by two independent observers. Two methods of CAD/CAM-assisted intraoral molding were compared: (i) stepwise manual design of molding plates (conventional CAD/CAM-intraoral molding) and (ii) a semi-automated approach with an automated detection of alveolar ridges (called RapidNAM) assisted by a graphical user interface (GUI). Both approaches significantly narrowed the clefts and resulted in a harmonic alveolar crest alignment. The GUI was easy to use and generated intraoral molding devices within minutes. The presented design solution is an efficient technical refinement with good clinical results. The semi-automated plate generation with a feasible GUI is fast but allows individual adaptations. This promising technique might facilitate and foster the more widespread use of CAD/CAM-technology in intraoral molding therapy.
EVALuna2:35085